COVID-19-Associated Thrombotic Complication: Is It Pulmonary Embolism or In Situ Thrombosis? - Rashid AL Umairi; Khadija AL Adawi; Maryam AL Khoori; Ahmed AL Lawati; Sachin Jose (Radiology Research and Practice)
Objectives. Acute pulmonary embolism is a protentional fatal complication of COVID-19. The aim of this study is to investigate whether pulmonary embolism is due to thrombus migration from the venous circulation to the pulmonary arteries or due to local thrombus formation secondary to local inflammation. This was determined by looking at the distribution of pulmonary embolism in relation to lung parenchymal changes in patients with COVID-19 pneumonia. Methods. Retrospectively, we identified pulmonary computed tomography angiography (CTPA) of patients admitted to the Royal Hospital between November 1st, 2020, and October 31, 2021, with a confirmed diagnosis of COVID-19. The CTPAs were examined for the presence of pulmonary embolism and the distribution of the pulmonary embolism in relation with lung parenchymal changes. Results. A total of 215 patients admitted with COVID-19 pneumonia had CTPA. Out of them, 64 patients had pulmonary embolisms (45 men and 19 women; mean age: 58.4 years with a range of 36–98 years). The prevalence of pulmonary embolism (PE) was 29.8% (64/215). Pulmonary embolism was more frequently seen in the lower lobes. 51 patients had PE within the diseased lung parenchyma and 13 patients had PE within normal lung parenchyma. Conclusion. The strong association between pulmonary artery embolism and lung parenchymal changes in patients admitted with COVID-19 pneumonia suggests local thrombus formation.